SISTEM INFORMASI MONITORING MURID OLEH GURU DENGAN ORANGTUA BERBASIS WEB DAN MOBILE - Sudono Widjaja; Bagus Mulyawan; Novario Jaya Perdana (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
In 2019, pandemic hits the world and the world was forced to change their way to do normal activities, including schools to do school activities from home. Elementary School children don’t yet know how to use devices properly therefore their parents have to help and guide them for them to understand the tasks given by school. The Information system for monitoring students expected able to help teachers and parents to coordinate and evaluate their student’s data. This system is made using two platforms, namely web-based whose main feature is for teacher to enter the students data, and mobile-based to view data that has been enetered from the web.